Photocatalytic Alkyl Addition to Access Quaternary Alkynyl alpha-Amino Esters - Kim, Juyeong; Lee, Jae Kyun; Moon, Bongjin; Lee, Ansoo (American Chemical Society, 2022)
A regioselective alkylation of beta,gamma-alkynyl-alpha-imino esters by visible-light photocatalysis has been developed. This method enables 1,2-addition of methyl, primary, secondary, and tertiary alkyl radicals to the conjugated imines under mild conditions to produce a variety of quaternary alkynyl alpha-amino acid and cyclic amino acid motifs. Alkyl radicals are generated from alkyl bis(catecholato)silicates with an organic photocatalyst. This process is effective under an air atmosphere, providing operational benefits compared to conventional alkylation using organometallic reagents.